P68 Phenotyping Infection Associated Asthma: A Case-Control Study. (12th November 2015) - Natarajan, S; Free, R; Wardlaw, A; Siddiqui, S
Abstract : Introduction and objectives: Asthmatics experiencing recurrent infective exacerbations, resembling a bacterial bronchitis, are often started on prophylactic antibiotics but this phenotype of asthma is not well understood. We sought to: a) compare asthmatics with and without recurrent infections using a case-control approach and b) phenotype asthmatics with recurrent infections to evaluate the heterogeneity within this population. Methods: We reviewed Leicester difficult asthma clinic letters within two calendar years (01/01/2013–31/12/2014) and utilised an asthma database to identify matched (age, sex, BMI and GINA treatment step) controls. Case definition: a clinician diagnosis of asthma and ≥2 respiratory tract infections/preceding year requiring oral antibiotics or on prophylactic antibiotics. Control definition: a clinician diagnosis of asthma, no evidence of recurrent infections and not prescribed prophylactic antibiotics. A 1:1 case-control ratio was used. 71 cases and 71 controls were identified. The antibiotic use, physiology, CT imaging, immunoglobulins and pneumococcal serotype metadata were evaluated. Model based cluster analysis was performed to phenotype the cases with no a priori assumption made on the number of clusters. Age, sex, age of onset, sputum eosinophil count and Juniper Asthma Control Score were used as the input variables (Am J Respir Crit Care Med.2008 Aug 1;178(3):218–24). Results: The cases were predominately female (69%), obese with recurrent infections (mean:4.25/preceding year) and had an impaired asthma-related quality life compared to controls (p = 0.0285). Cluster analysis identified three groups. Cluster 1: male, eosinophilic, on oral corticosteroids with a low IgM, had poor lung function and bronchial wall thickening and bronchiectasis on CT. Cluster 2: female with a blood neutrophilia and preserved lung function. Cluster 3: female, non-atopic with impaired asthma control, a low IgG and air trapping on CT. 63.3% of patients on prophylactic antibiotics (n = 49) had a reduction in infective exacerbation frequency. The proportion of patients on antibiotics within each cluster and response was similar. Conclusion: Three subphenotypes of asthma with recurrent infections have been identified. Further immunpathological studies to evaluate the mechanism of infection in each subphenotype, the host microbiome and response to antimicrobials are required.